Exploring enabling factors for innovation outcomes. A firm-level analysis of Peruvian companies (2020)
Most innovation research has been primarily focused on developed countries, creating a gap in the literature related to innovation processes in emerging markets, such as Latin America. Even as some studies aim at this region, their approach is usually conducted from the standpoint of a R+D funding perspective only. This paper aims to discuss the relationship between resources for innovation and sources of innovation with innovation outcomes, using a sample of Peruvian companies that received public funds for the development of innovative activities. This study found evidence that resources for innovation and sources of innovation have a positive influence on innovation outcomes. Moreover, resources for innovation are related to non-technological innovation, although internal R+D is the most frequently used by companies, even when it is not related to product, nor to process innovation. Sources of innovation are related to product innovation and firms have shown an incipient use of inter-firm collaboration strategies to gain access to them.